2018
DOI: 10.1177/0092055x18760691
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sociology Majors to Labor Market Success

Abstract: Colleges and universities face pressures from multiple stakeholders to attend to the labor market success of their graduates. In this article, we argue that it is in the best interests of sociology students and the discipline that sociology programs respond proactively to these pressures. We encourage sociology programs to design curricula that develop student skills in critical sociological thinking as well as explicitly connect skills to career-related interests. After reviewing research on what employers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Yet an increasing number of collegiate programs encourage or require internship participation for graduation, raising questions about the consequence for students with fewer existing job skills or students who are unable to participate due to financial constraints The same is true within the discipline of sociology. Internships have been touted as a way for faculty to facilitate students' labor market success (Ciabattari et al 2018) and for students to put their sociology degrees to work (Joseph 2017). A recent survey by the American Sociological Association ([ASA] 2018b) found that "virtually all sociology departments (91 percent) reported offering internships to their undergraduates".…”
Section: Discussionmentioning
confidence: 99%
“…Yet an increasing number of collegiate programs encourage or require internship participation for graduation, raising questions about the consequence for students with fewer existing job skills or students who are unable to participate due to financial constraints The same is true within the discipline of sociology. Internships have been touted as a way for faculty to facilitate students' labor market success (Ciabattari et al 2018) and for students to put their sociology degrees to work (Joseph 2017). A recent survey by the American Sociological Association ([ASA] 2018b) found that "virtually all sociology departments (91 percent) reported offering internships to their undergraduates".…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the National Association of Colleges and Employers (NACE) argues that all college graduates need to have mastered eight career readiness competencies (NACE 2019). While there is strong overlap between the skills learned in sociology programs and these skills in demand by employers, it is more likely that sociology programs emphasize a competency, such as “critical thinking/problem solving” or “global/intercultural fluency,” than others, such as “career management” or “digital technology” (Ciabattari et al 2018). The NACE Career Readiness Initiative suggests the importance of “career management” so that graduates can “identify and articulate one’s skills, strengths, knowledge, and experiences relevant to the position desired and career goals, and identify areas necessary for professional growth” (NACE 2019).…”
Section: Why Courses On Careers For Sociology Majors Are Neededmentioning
confidence: 99%
“…I then discussed the literature on what employers seek in college graduates, highlighting the Career Readiness Initiative from NACE (2019) and the strong overlap between the skills learned in sociology programs and the skills in demand by employers (Ciabattari et al 2018). I also introduced them to the Bachelor’s and Beyond studies that show both that sociology majors do learn important skills that they use on their jobs and that the majors who use those skills are both more satisfied with their jobs and more likely to be on a career track (Senter, Spalter-Roth, and Van Vooren 2015).…”
Section: Course Outline and Assignmentsmentioning
confidence: 99%
“…In this context, social and political characteristics might also refer to different motivations to study sociology in general and different orientations toward the labor market. Such differences in motivation, attitude, and expectations between social groups are not systematically considered so far in the discussion of the relation between choosing majors and labor market success of sociology students (McKinney and Naseri 2011; Ciabattari et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%